Experiments using a novel penetrometer to assess changing strength of clay during remolding and reconsolidation - Fauzan, Sahdi; White, D. J.; Gaudin, Christophe (American Society of Civil Engineers (ASCE), 2017)
The process of remolding and subsequent recovery of soil shear strength is a common geotechnical problem, especially in the offshore environment, where foundations and pipelines are subjected to intermittent operational and environmental loads. A novel vertically oriented penetrometer (VOP) was used in a centrifuge testing program to study the changing strength of normally consolidated kaolin from successive disturbance and reconsolidation events. The VOP is used to determine soil shear strength via an interpretation akin to the laterally loaded pile. The test series involved cyclic movement of the VOP at velocities ranging from 0.3 to 3 mm/s, with a corresponding 100-fold variation in the duration of each cycle. For the VOP tests at low velocities with high cyclic periods, the soil resistance initially reduces, but then shows an increase that scales with the elapsed time, indicating reconsolidation. Ultimately, if the cycling continues for sufficient time, the recovery in strength from reconsolidation can exceed the weakening from remolding. A previously published framework using critical-state soil mechanics concepts is shown to capture the changing resistance well.